ОСОБЛИВОСТІ ПЕРЕХІДНИХ ХАРАКТЕРИСТИК ВИМІРЮВАЛЬНИХ СИСТЕМ ВИСОКОВОЛЬТНИХ ІМПУЛЬСІВ ПРИ ЗНАЧНІЙ ДОВЖИНІ КАБЕЛЬНОГО ПРИЄДНАННЯ - Бржезицький, В.О.; Козюра , В.В. (Інститут електродинаміки НАН України, Київ, 2012)
Studies, based on mathematical modelling, has found features of transient characteristics taking proper account of which may greatly increase accuracy of dividers characteristics determination. References 3, figures 2.